Indonesia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper takes stock of Indonesia's performance against the original macroeconomic objectives under the IMF's extended arrangement. The paper compares the performance of the Indonesian economy in the post-crisis period with that of the other major 'crisis' countries in the region. It reviews the background to the current extended arrangement and describes the core macroeconomic objectives of the program. The paper also considers Indonesia's performance against objectives for growth, inflation, the balance of payments, and improving Indonesia's debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet